Prevalence of Smoking Among Secondary School Students in Sarawak - Juslina, O (Academy of Family Physician of Malaysia, 2011)
Adolescent smoking is an emerging health concern in the developing countries. A cross-sectional study is conducted to determine the prevalence and smoking behaviour of adolescents in Sarawak. The prevalence of smoking is 32.8% with mean age of initiation at 12.8±1.9 years. Most (67.2%) adolescents are experimental smokers and the majority (67.9%) did not smoke on a daily basis. Branded cigarettes are preferred (83.1%) and the cigarettes are obtained either from friends (49.1%) or self purchased (43.6%). Students prefer to smoke at their friend’s house (31.0%) or at school (25.3%). Smoking prevalence among adolescents in Sarawak is high and begins early. Early intervention on smoking prevention and risk awareness is perhaps more effective if initiated before the age of 12 years.